Description of the Level of Knowledge and Attitudes of YARSI University Faculty Of Medicine Student Batch 2019 About Basic Life Support And Its Overview According To Islam - Ardini, Putri; Ferlianti, Rika; Arifandi, Firman; Syam, Edward (Junior Medical Journal, 2023)
Background: Cardiac arrest is one of the emergency conditions that can be life-threatening and requires immediate intervention. According to the American Heart Association in 2015, approximately 350,000 adults in the United States have nontraumatic cardiac arrest outside the hospital (out-of-hospital cardiac arrest (OHCA) and are handled by Emergency Medical Services/EMS. The first treatment for cardiac arrest is Basic Life Support (BLS) which is not only carried out by health workers such as doctors/nurses and EMS, but every community in general can do BLS. However, several studies in Indonesia show the low level of knowledge, including medical students about BLS. Method: The type of research used is descriptive quantitative survey method using a questionnaire. The population of this study were students of the Faculty of Medicine, YARSI University Class of 2019 according to the inclusion and exclusion criteria. A sample of 174 people used consecutive sampling which was conducted on 20 October 2022 – 7 November 2022. Results: Percentage based on high level of knowledge (14.94%), sufficient level of knowledge (38.5%), and low level of knowledge (46.6%). Percentage based on very good attitude level (17.24%), good attitude level (64.37%), sufficient attitude level (17.83%), low attitude level (0.57%). Conclusion: The majority of students have a low level of knowledge and good attitude level.